Analisis Pengaruh Website www.cibuntu.com Terhadap Brand Awareness Desa Wisata Cibuntu Kabupaten Kuningan - Welli Braham (Program Studi Hospitality dan Pariwisata, 2017)
The development of more advanced computerized technology and its benefits became more apparent, with the internet making communication easier. The website is one of the prevalent means of promotion used by marketers today. In its development, Tourism Village of Cibuntu also not spared in making use of the Internet particular functions of the website. Www.cibuntu.com website is expected to help both the management and other relevant parties to exchange relevant information Cibuntu Tourism Village. This study will identify how the views of respondents to www.cibuntu.com website and its influence on brand awareness of Cibuntu Tourism Village. Key words: Tourism Village, website, brand awareness